Structure–Activity Relationship Studies of Amino Acid Substitutions in Radiolabeled Neurotensin Conjugates. Issue 1 (23rd November 2015) - Mascarin, Alba; Valverde, Ibai E.; Mindt, Thomas L.
Abstract: Radiolabeled derivatives of the peptide neurotensin (NT) and its binding sequence NT(8–13) have been studied as potential imaging probes and therapeutics for NT‐1‐receptor‐positive cancer. However, a direct comparison of reported NT analogues, even if radiolabeled with the same radionuclide, is difficult because different techniques and models have been used for preclinical evaluations. In an effort to identify a suitable derivative of NT(8–13) for radiotracer development, we herein report a side‐by‐side in vitro comparison of radiometallated NT derivatives bearing some of the most commonly reported amino acid substitutions in their sequence. Performed investigations include cell internalization experiments, determinations of receptor affinity, measurements of the distribution coefficient, and blood serum stability studies. Of the [ 177 Lu]‐1, 4, 7, 10‐tetraazacyclododecane‐1, 4, 7, 10‐tetraacetic acid (DOTA)‐labeled examples studied, analogues of NT(8–13) containing a short hydrophilic tetraethylene glycol (PEG4 ) spacer between the peptide and the radiometal complex, and a minimum number of substitutions of amino acid residues, exhibited the most promising properties in vitro. Abstract : A level playing field : Standardized experimental conditions for the preclinical in vitro evaluation of radiolabeled neurotensin [NT(8–13)] derivatives enabled a thorough structure–activity relationship study of the effects of commonly applied amino acid substitutions on the biological properties of these tumor‐targeting peptide conjugates.